Pendampingan Pemanfaatan Digitalisasi Augmented Reality Sebagai Media Pembelajaran Interaktif Pada SDN Wonorejo 1 Kab Blitar - Mohammad Faried Rahmat; Rizki Dwi Romadhona; Nabillah Rachelia Meyshita (P3M Politeknik Negeri Malang, 2024)
Technological developments in the field of interactive learning media have now experienced significant progress. The development of this technology does not only facilitate the delivery of one-way information. But it provides opportunities for educators and students to explore learning more interactive and interesting. One of the latest learning media technologies is Augmented Reality. This technology offers the merging of the physical world and virtual elements that are attractive to users. The method in this study uses applied research. for this application development method using the MDLC method or Multimedia Development Life Cycle. For testing in this study is divided into two namely testing based on application functions using the blackbox method and testing using a questionnaire as an evaluation of the use of AR as a determination of conclusions. Based on the results of blackbox testing, a number of 100% is obtained which indicates that this application does not experience problems in using the functions of the features offered. For the results of questionnaire testing obtained an increase in student motivation by 70% which has a high motivation to learn Augmented Reality-based learning. Based on these tests it can be concluded that Augmented Reality Technology and Quizzes can increase student learning motivation.